A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae – Grewioideae) - Wellsow, Julia; Hart, Michelle; Wilkie, Peter; Harris, David J. (European Journal of Taxonomy, 2019)
A taxonomic revision of Desplatsia Bocq. (Malvaceae s. lat. Juss., subfamily Grewioideae Hochr., tribe Grewieae Endl.) based on about 800 herbarium specimens is presented. Desplatsia is a genus of trees and shrubs found in tropical West and Central Africa and is characterized by subulately divided stipules, the absence of an androgynophore, stamens that are fused to a tube at the base, and large and distinctive fruits that are dispersed by elephants. Four species are recognized (D. subericarpa Bocq., D. chrysochlamys (Mildbr. & Burret) Mildbr. & Burret, D. dewevrei (De Wild. & T.Durand) Burret and D. mildbraedii Burret) and 12 species names are placed into synonymy, two of which have been put into synonymy for the first time: D. floribunda Burret syn. nov. and D. trillesiana (Pierre ex De Wild.) Pierre ex A.Chev. syn. nov. All four species are widely distributed and their conservation status is assessed as Least Concern (LC). A key to the species, full species descriptions, illustrations, a specimen citation list and distribution maps are provided.